2021
DOI: 10.2147/rmi.s292961
|View full text |Cite
|
Sign up to set email alerts
|

CT and MRI Findings of Head and Neck Masson’s Tumor: A Rare Case Report and Systematic Review of the Literature

Abstract: Background: Masson's tumor (MT) is a rare benign vascular disease. In literature, detailed description of its radiological findings is not available and functional imaging such as diffusion weighted (DW)-MRI has never been described. We aim to summarize the CT and MRI findings in our representative case and to conduct a systematic review of the literature. Case Presentation: We reported a 54-year-old ex-smoker male patient who presented with a nodular mass to the left cheek. He denied any previous trauma. CT e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Awell-defined mass with high or soft tissue density is a common computed tomographic finding, whereas MRI findings frequently include nonhomogeneous signal intensity in T1-and T2-weighted sequences, with foci of hyperintensity, multiple septations, or flow voids. 15 In the MRI enhancement studies, most showed either heterogeneous or rim enhancement. 16 Our case also showed a heterogeneous enhancement pattern.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Awell-defined mass with high or soft tissue density is a common computed tomographic finding, whereas MRI findings frequently include nonhomogeneous signal intensity in T1-and T2-weighted sequences, with foci of hyperintensity, multiple septations, or flow voids. 15 In the MRI enhancement studies, most showed either heterogeneous or rim enhancement. 16 Our case also showed a heterogeneous enhancement pattern.…”
Section: Discussionmentioning
confidence: 98%
“…On ultrasonography and Doppler ultrasound, IPEH appears as a well-defined, heterogeneously hypoechogenic lesion with varying degrees of vascularity. A well-defined mass with high or soft tissue density is a common computed tomographic finding, whereas MRI findings frequently include nonhomogeneous signal intensity in T1- and T2-weighted sequences, with foci of hyperintensity, multiple septations, or flow voids 15 . In the MRI enhancement studies, most showed either heterogeneous or rim enhancement 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In 30% of cases, it is related to trauma or vascular abnormalities (eg, hemangiomas, vascular malformations, pyogenic granulomas, blood stasis) that induce a perivascular inflammation and favor the onset of a reactive process by endothelial cells through a consistent secretion of FGF-β [ 5 ]. However, the trigger stimulus is still not clear, so the etiology remains unknown [ 5 , 15 , 40 ]. Salyer et al found a peculiar pattern of thrombus organization [ 28 , 41 ].…”
Section: Discussionmentioning
confidence: 99%